The manufacture of gummed wax seals in the Middle Ages: a study of a fourteenth-century technical recipe from the Biblioteca Nacional de España - Díaz Hidalgo, Rafael Javier (En la España Medieval, 2022)
Wax seals, whether pendant or affixed en placard, were essential elements of past societies, particularly medieval and early modern ones. However, discussion of the make-up and manufacture of seals rarely appears in works of sigillography, apart from brief considerations of ingredients and colouring. Responding to this lacuna, this work considers the manufacture and make-up of one particular type of seal, the gummed wax seal, that emerges with the widespread adoption of paper in the Iberian kingdoms in the middle of the thirteenth century. Using a recipe for gummed wax seals preserved in the Biblioteca Nacional de España, this piece sets out the technical processes used in the making of the material that would receive the impression of the seal matrix.
Keywords: manufacture of stamps; medieval science and technique; medieval technical recipes; wax; pine resin; vermilion